Ocular neuroinflammatory response secondary to SARS-CoV-2 infection-a review - Zhao, Yun; Tang, Ying; Wang, Qi Yao; Li, Jia (Frontiers in Immunology, 2025)
With the consistent occurrence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, the prevalence of various ocular complications has increased over time. SARS-CoV-2 infection has been shown to have neurotropism and therefore to lead to not only peripheral inflammatory responses but also neuroinflammation. Because the receptor for SARS-CoV-2, angiotensin-converting enzyme 2 (ACE2), can be found in many intraocular tissues, coronavirus disease 2019 (COVID-19) may also contribute to persistent intraocular neuroinflammation, microcirculation dysfunction and ocular symptoms. Increased awareness of neuroinflammation and future research on interventional strategies for SARS-CoV-2 infection are important for improving long-term outcomes, reducing disease burden, and improving quality of life. Therefore, the aim of this review is to focus on SARS-CoV-2 infection and intraocular neuroinflammation and to discuss current evidence and future perspectives, especially possible connections between conditions and potential treatment strategies.